PENGARUH PENGGUNAAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR MATERI TERMODINAMIKA - Siringo, Sakkot Parulian; Asmaidah, Seri; Rozi Nasution, Sari Wahyuni (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to know whether there is a significant difference of using GI (Group Investigation) and lecture learning model on student’ physic achievement on the topic thermodynamics at eleventh grade students of SMA. The research was conducted by using experimental method with 50 students as the sample and they were taken by using total sampling technique. GI learning model was experimental class and lecture learning model was control class and each class had 25 students as the sample. Test and observation were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using GI learning model was 80.24 (very good category) and b) the average of student’ physic achievement on the topic thermodynamics before using GI learning model was 52.04 (enough category) and after using GI learning model was 71.82 (good category). Furthermore by using inferential statistic by using ttest two tails, it could be found ttable was less than tcalculated (1.71< 6.85). It means, there is a significant difference of using GI (Group Investigation) learning model and lecture model on student’ physic achievement on the topic thermodynamics at eleventh grade students of SMA. Key words: Group Investigation (GI), Achievement, and Thermodynamics